Investigating the Impact of Establishing Integrated Management Systems on Accidents and Safety Performance Indices: A Case Study - Fereydoon Laal; Mostafa Pouyakian; Rohollah F. Madvari; Amir H. Khoshakhlagh; Gholam H. Halvani (Elsevier, 2019)
Background: Increasing the establishment of integrated management systems (IMSs) is done with the purpose of leaving traditional management methods and replacing them with modern management methods. Thus, the present study sought to analyze the events and investigate the impact of IMS on health and safety performance indices in an Iranian combined cycle power plants. Methods: This case study was conducted in 2012 in all units of the Yazd Combined Cycle Power Plant on accident victims before and after the implementation of IMS. For data analysis and prediction of indices after the implementation of IMS, descriptive statistics and Kolmogorov-Smirnov test, Chi-square, linear regression, and Cubic tests were conducted using SPSS software. Results: The number of people employed in the power plant in an 8-year period (2004-2011) was 1,189, and 287 cases of work-related accidents were recorded. The highest accident frequency rate and accident severity rate were in 2004 (32.65) and 2008 (209), respectively. Safe T-score reached to below −3 during 2010-2011. In addition, given the regression results, the relation between all predictor variables with outcomes was significant (p < 0.05), except for the variable X1 belonging to the accident severity rate index. Conclusion: The implementation of safety programs especially that of IMS and its annual audits has had a significant impact on reducing accident indices and improving safety within the study period. Accordingly, health and safety management systems are appropriate tools for reducing accident rate, and the use of regression models and accident indices is also a suitable way for monitoring safety performance. Keywords: Integrated management systems, Occupational accident, Power plant, Safety performance indices